2022
DOI: 10.1021/acsnano.1c09374
|View full text |Cite
|
Sign up to set email alerts
|

Robust Atomic-Resolution Imaging of Lithium in Battery Materials by Center-of-Mass Scanning Transmission Electron Microscopy

Abstract: The performance of energy storage materials is often governed by their structure at the atomic scale. Conventional electron microscopy can provide detailed information about materials at these length scales, but direct imaging of light elements such as lithium presents a challenge. While several recent techniques allow lithium columns to be distinguished, these typically either involve complex contrast mechanisms that make image interpretation difficult or require significant expertise to perform. Here, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…iDPC is a technique that maps the center‐of‐mass (COM) of the transmitted electron probe [ 33 ] and as such, is a linear contrast mechanism that can be used to simultaneously image both light and heavy elements in well‐oriented crystals, including Li in layered Mn oxide batteries. [ 34 ] Similar to LNMA10, both the M‐phase and R‐phase are readily identifiable in this image. However, in contrast, these phases are not present as nanodomains but, rather, are morphologically confined to the surface (R‐phase) and bulk (M‐phase).…”
Section: Resultsmentioning
confidence: 70%
“…iDPC is a technique that maps the center‐of‐mass (COM) of the transmitted electron probe [ 33 ] and as such, is a linear contrast mechanism that can be used to simultaneously image both light and heavy elements in well‐oriented crystals, including Li in layered Mn oxide batteries. [ 34 ] Similar to LNMA10, both the M‐phase and R‐phase are readily identifiable in this image. However, in contrast, these phases are not present as nanodomains but, rather, are morphologically confined to the surface (R‐phase) and bulk (M‐phase).…”
Section: Resultsmentioning
confidence: 70%
“…In a recent paper published by Zachman et al, 4D-STEM imaging with advancements in data analysis was demonstrated to successfully image the atomic structure and interfacial charge transfer simultaneously for the first time. Moreover, the 4D-STEM technique can even be used to image light elements such as lithium atoms …”
Section: Integration Of New Electron Microscopy Techniquesmentioning
confidence: 99%
“…Moreover, the 4D-STEM technique can even be used to image light elements such as lithium atoms. 307 With 4D-STEM, 306 one can capture ADF, BF, and CoM in tandem to uncover both structural and chemical information. In particular, the CoM of the electron beam intensity in the detector plane retains information on internal fields as it measures the momentum transfer from the specimen to the electron probe.…”
Section: Measuring Charge Transfer In Heterogeneous Catalysts Using 4...mentioning
confidence: 99%
“…By capturing most of the diffracted electrons on a pixelated detector, 4D-STEM allows for complex data analysis without physical hardware constraints. It offers the flexibility of reconstructing annular detector images in any arbitrary collection range and enables enhanced spatial resolution in both the lateral and depth directions via ptychographic reconstruction. , More importantly, 4D-STEM captures symmetry breaks within the sample and electron momentum transfer, which reveal important features such as charge distribution, ferroelectric polarization, magnetism, and the position of light elements without the need for specialized detectors. This ability makes 4D-STEM an ideal technique to explore quantum materials, where the correlation between spin, charge, and lattice may cause exotic phenomena, which are otherwise difficult to characterize . However, most quantum phenomena occur at low temperatures, thus necessitating cryogenic cooling of the specimen.…”
Section: Introductionmentioning
confidence: 99%